EVALUATING RISK FACTORS OF BEING OBESE, BY USING ID3 ALGORITHM IN WEKA SOFTWARE - Qendraj, Daniela; Xhafaj, Evgjeni (European Scientific Journal, ESJ, 2015)
Id3 algorithm is used for building a decision tree from a fixed set of examples, next step is an iterative way that uses the resulting tree to classify future examples. Nowdays the large amount of data needs to be classified into useful information. Being obese refers to an excessive accumulation of body fat. The aim of this paper is to construct a decision tree with Id3 algorithm, by the data collect from Tirana Inter-medical Centre, analyzing the factors that makes the patients obese.